HUBUNGAN BREASTFEEDING SELF EFFICACY TERHADAP LAMANYA MENYUSUI PADA IBU NIFAS WILAYAH KERJA PUSKESMAS SUMUR BATU KOTA BANDAR LAMPUNG - Dina Astuti br Sinaga; Anita Bustami (Malahayati Nursing Journal, 2020)
ABSTRACT : RELATIONSHIP BETWEEN SELF EFFICACY BREASTFEEDING ON LIGHTING IN BREASTFEEDING IN PREGNANT WOMEN WORK OF PUSKESMAS SUMUR BATU KOTA BANDAR LAMPUNG 2019 Background : Giving ASI immediately after giving birth has many benefits for mother and child. The achievement of exclusive breastfeeding in Lampung Province in 2016 amounted to 56.26% where the highest achievement in Mesuji Regency was 85.28% and the lowest was in Tulang Bawang District by 32.51% while Bandar Lampung City was 58.89% even though it was still above the Provincial Achievement but this is far from the target of a strategic plan of 80% while achieving exclusive breastfeeding.Purpose : the relationship between breastfeeding self efficacy and the duration of breastfeeding in postpartum mothers in the Work Area of Sumur Batu Bandar Lampung Health Center in 2019 is known.Methods : Type of quantitative research, analytic research design with cross sectional approach. The population were all postpartum mothers, postpartum maternal samples in the Sumur Batu Bandar Lampung Community Health Center Working Area, the time of the study was conducted in 22 Apri - May 22, 2019. Objects in length of breastfeeding for postpartum mothers before and after breastfeeding self efficacy were given. Retrieving data with a questionnaire using breastfeeding self efficacy. Data analysis was univariate (average) and bivariate (using t-test).Result : It is known that most of the respondents breastfeed for a longer period of time 15/30 minutes, which is as many as 28 (60.9%) respondents. It is known that most of the Breastfeeding Self Efficacy respondents were 58.61, which was less than 30 (65.2%) respondents. There is a relationship between breastfeeding self efficacy and the duration of breastfeeding in postpartum mothers in the Sumur Batu Bandar Lampung Community Health Center Working Area in 2019 (p-value = 0.001: OR 12,000). Keywords      : Breastfeeding Self Efficacy, postpartum mother, breastfeeding, exclusive breastfeeding ABSTRAK Latar Belakang:Pemberian ASI segera setelah melahirkan memberikan banyak manfaat bagi ibu dan anak. Pencapaian ASI eksklusif di Provinsi Lampung tahun 2016 sebesar 56,26% dimana  pencapaian tertinggi di Kabupaten Mesuji sebanyak 85,28% dan terendah di Kabupaten Tulang Bawang sebesar 32,51% sedangkan Kota Bandar Lampung sebanyak 58,89% walaupun masih di atas pencapaian Provinsi namun ini jauh dari target renstra sebesar 80% sedangkan pencapaian ASI eksklusif.Tujuan Penelitian:diketahui hubungan breastfeeding self efficacy dengan lamanya menyusui pada ibu nifas di Wilayah Kerja Puskesmas Sumur Batu Bandar Lampung Tahun 2019.Metode Penelitian : Jenis penelitian kuantitatif, desain penelitian analitik dengan pendekatan cros sectional. Populasi adalah semua ibu nifas, sampel ibu nifas di Wilayah Kerja Puskesmas Sumur Batu Bandar Lampung, waktu penelitian telah dilaksanakan bulan 22 Apri – 22 Mei 2019. Objek dalam lamanya menyusui pada ibu nifas sebelum dan sesudah diberikan  breastfeeding self efficacy. Pengambilan data dengan kuesioner mengunakan breastfeeding self efficacy. Analisis data secara univariat (rata-rata) dan bivariat (menggunakan t-test).Hasil penelitian : Diketahui sebagian besar responden lama menyusui kurang baik 15/30 menit, yaitu sebanyak 28 (60,9%) responden.Diketahui sebagian besar responden Breastfeeding Self Efficacy kurang baik 58,61, yaitu sebanyak 30 (65,2%) responden.Ada hubungan breastfeeding self efficacy dengan lamanya menyusui pada ibu nifas di Wilayah Kerja Puskesmas Sumur Batu Bandar Lampung Tahun 2019 (p-value = 0,001 : OR 12,000). Kata kunci     : Breastfeeding Self Efficacy, ibu nifas, menyusui, asi eksklusif